Evaluation of chickpea genotypes against Fusarium wilt for resistant sources - N. SRINIVASA, S.C. DUBEY*, BIRENDRA SINGH and (Indian Phytopathology, 2017)
Wilt caused by Fusarium oxysporum f. sp. ciceris is an important yield limiting disease of chickpea. Cultivation of resistant cultivars is an economical management option available for the disease. Six hundred sixty eight genotypes of chickpea were screened against F. oxysporum f. sp. ciceris in sick field for three years from 2013-14 to 2015-16 crop season. The genotypes SCGP-WR 28, H 10-05, GL 10023, IPC 2006-77 and CSJK 72 were found to be resistant and the genotypes H 09-70, H 08-25, H 10-16, DCP 92-3, GNG 1936 and Pusa 212 proved to be moderately resistant against the wilt. The remaining genotypes showed susceptible reaction against the disease. These genotypes could be cultivated as such or used as resistance source in breeding programme.